Eurobond Performance in Emerging Markets: Do Economic Freedom, Contagion Effects, and Strategic International Relations Matter? - El Rouby, Nourhan (AUC Knowledge Fountain, 2024)
This paper studies the factors moving the Eurobond prices and credit ratings issued by emerging markets. By observing a set of variables, including economic freedom, contagion effects and strategic international relations, the study was able to provide a thorough analysis of their impact on Eurobond performance. The research was able to identify significant determinants of Eurobond prices and credit ratings through utilizing panel data from 20 emerging markets over a period of April 2018 to September 2023 where we applied fixed effects linear regression and ordered logit models. The findings resulted that economic freedom, in specific enforcement of contracts, and strategic international relations significantly influence Eurobond performance. The robustness of the research results shows the importance of the mentioned variables in knowing the dynamics of Eurobond markets. The insights attained from this study can support policymakers in applying strategies to improve the financial stability and moderate risks related to Eurobond investments.